A Loading Dose of Dexmedetomidine With Constant Infusion Inhibits Intraoperative Neuromonitoring During Thoracic Spinal Decompression Surgery: A Randomized Prospective Study - Tun Liu; Yue Qin; Huaguang Qi; Zhenguo Luo; Liang Yan; Pengfei Yu; Buhuai Dong; Songchuan Zhao; Xucai Wu; Zhen Chang; Zhian Liu; Xuemei Liu; et al. (Frontiers Media S.A., 2022)
Background: The effect of a bolus dose of dexmedetomidine on intraoperative neuromonitoring (IONM) parameters during spinal surgeries has been variably reported and remains a debated topic.Methods: A randomized, double-blinded, placebo-controlled study was performed to assess the effect of dexmedetomidine (1 μg/kg in 10 min) followed by a constant infusion rate on IONM during thoracic spinal decompression surgery (TSDS). A total of 165 patients were enrolled and randomized into three groups. One group received propofol- and remifentanil-based total intravenous anesthesia (TIVA) (T group), one group received TIVA combined with dexmedetomidine at a constant infusion rate (0.5 μg kg−1 h−1) (D1 group), and one group received TIVA combined with dexmedetomidine delivered in a loading dose (1 μg kg−1 in 10 min) followed by a constant infusion rate (0.5 μg kg−1 h−1) (D2 group). The IONM data recorded before test drug administration was defined as the baseline value. We aimed at comparing the parameters of IONM.Results: In the D2 group, within-group analysis showed suppressive effects on IONM parameters compared with baseline value after a bolus dose of dexmedetomidine. Furthermore, the D2 group also showed inhibitory effects on IONM recordings compared with both the D1 group and the T group, including a statistically significant decrease in SSEP amplitude and MEP amplitude, and an increase in SSEP latency. No significance was found in IONM parameters between the T group and the D1 group.Conclusion: Dexmedetomidine delivered in a loading dose can significantly inhibit IONM parameters in TSDS. Special attention should be paid to the timing of a bolus dose of dexmedetomidine under IONM. However, dexmedetomidine delivered at a constant speed does not exert inhibitory effects on IONM data.